Experimental study on disassembly of adhesively bonded composite joints using thermally expandable particles - Syabil Amasha (Nanyang Technological University, 2021)
In recent years, the use of Fibre Reinforced Polymers (FRP) has increased tremendously due to their ability to withstand tremendous forces displaying lightweight properties. In automotive industries, such composite materials are used in cars, boats, and planes to reduce weight. This in turn makes products that are more economical and thus environmentally friendly. However, in such complex composite structures, adhesive bonding is a better alternative to mechanical fasteners due to unintended stress formed during any mechanical action. Adhesive bonds are strong yet permanent in nature, making separation difficult to achieve. In a scenario where repair access is hindered by such bonded structures, destruction of the composite material is necessary. With sustainability, such a key issue in today’s modern world, developing a successful debonding mechanism will reduce composite waste and thus help save the environment. Therefore, the overall aim of the study is to obtain a high-performance adhesive that shows ideal debonding ability through modification of the adhesive system. The adhesive modification selected is the addition of Thermally Expandable Particles (TEPs) mixed into the epoxy. These microparticles are activated thermally when exposed to an external heat source, causing expansion. Eventually, this leads to the formation of micro-fractures within the adhesive bonds. By using various concentration of TEPs mixed into the epoxy, the debonding ability of modified adhesive bonds can then be determined. To quantify the impact of TEPs with regards to the debonding ability, multiple preliminary tests are conducted. Analysis under Scanning Electron Microscopy of the heated TEPs at various temperatures and heating rates allows for a better understanding of the debonding mechanism in play. Additionally, various thermal tests are conducted to decide the ideal heating temperature to allow for maximum debonding. The shear strength of the joint is then tested to assess the influence of the TEP- epoxy mixture onto the debonding ability of the single lap joints. Assessment of the bonded single lap joints are carried out by subjecting it to tensile forces as per ASTM D5868. The single-lap shear tests are performed with varying content of Expancel 043 DU 80 (0wt.%, 5wt.%, 10wt.%,15wt.%). Based on the obtained experimental results, a 10wt.% TEPs-modified epoxy with plasma-treated GFRP adherends displayed the best debonding ability while providing almost no fibre-tearing at previously bonded regions.